Perancangan Interior Butik dan Kafe âTOPSHOPâ di Surabaya - Fenny Kurnia Dewi, Jessica Cynthia Haryono Hedy C. Indrani (Intra, 2013)
Development of fashion and culinary in Indonesia is growing rapidly. Boutiques and cafes are very identical to human life. For this design of Topshop boutique and cafÃ© in Surabaya have some facilities such as boutiques, cafes, fashion show area, nail art station, clothing reparation area and childrenâs play area. The concept is âOxford Streetâ which is the name of the first place that Topshop was established, in London. The atmosphere that want to be created in this design is the atmosphere of city street which is surrounded by shop, cafÃ© and another public facilities are also widely encountered along the way.